Leptomeningeal carcinomatosis: a clinical dilemma in neuroendocrine neoplasms - Apostolidis, Leonidas; Schrader, Jörg; Jann, Henning; Rinke, Anja; Krug, Sebastian (Biology, 2021)
Central nervous system (CNS) involvement by paraneoplastic syndromes, brain metastases, or leptomeningeal carcinomatosis (LC) in patients with neuroendocrine neoplasms (NEN) has only been described in individual case reports. We evaluated patients with LC in four neuroendocrine tumor (NET) centers (Halle/Saale, Hamburg, Heidelberg, and Marburg) and characterized them clinically. In the study, 17 patients with a LC were defined with respect to diagnosis, clinic, and therapy. The prognosis of a LC is very poor, with 10 months in median overall survival (mOS). This is reflected by an even worse course in neuroendocrine carcinoma (NEC) G3 Ki-67 >55%, with a mOS of 2 months. Motor and sensory deficits together with vigilance abnormalities were common symptoms. In most cases, targeted radiation or temozolomide therapy was used against the LC. LC appears to be similarly devastating to brain metastases in NEN patients. Therefore, the indication for CNS imaging should be discussed in certain cases.
Gesehen am 26.05.2021